The Components of Dengue Haemorrhagic Fever (DHF) Surveillance System in Health Department of Kediri City - Mahfudhoh, Binti (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTThe Dengue Haemorrhagic Fever (DHF) was the dangerous infectious disease because it could cause fatality. Kediri City was the DHF endemic area. The Incident Rate in 2013 was about 99,28 per 100.000 population and CFR 0,73%. Effort to overcome DHF in Kediri City was implementing the better epidemiology surveillance system that able to monitor the desease regularly and continuously. The purpose of this research was to evaluate the implementation of DHF surveillance in Health Department of Kediri City. This research used the descriptive method with cross sectional design. Respondent was the functionary of DHF surveillance programme in Health Departement. Data resources consist of primer data and secondary data. The result of the research shown that data collection of DHF surveillance were routine and non-routine data, manpower and tools were sufficient, data collection method were active and passive, the frequency of data collection were monthly, quarterly, and incidentally. Punctuality was uncountable, the completeness of data were 47,9%, and the DHF form were sufficient. Data compilation based on people, time, place, and endemic area. Data analysis based on morbidity, mortality, and area stratification. Data interpretation consist of comparative analysis, coverage analysis, and kecenderungan analysis. The epidemiology information were the general information of DHF. Information dissemination were reporting of the DHF data to Health Department of East Java province and feedback to the public health center.Keywords: DHF, evaluation, surveillance, Kediri City